(untitled) (Journal of Spatial Planning and Design, 2021)
Eğirdir districts is rich in natural and historical environmental values and cultural traits are the important places of tourism and recreational activities. Tourism and recreational activities, which are developed in regards with the atractiveness of such places, are made of those natural and cultural environment. When events of tourism all over the world are examined, it could be observed that such activities usually take place during summer months. However, since developing residences and facilities tend to use sources more than before, they affect natural, historical and the cultural values negatively and thus corruption starts. Inspite of the fact that the district is gradually getting more intensive in terms of tourism and recreation during the four seasons, there haven’t been any serious problems yet. In the areas of these natural and cultural resources, the problems related with the use of those resources where tourism and recreational activities are concentrated can not be ignored and the purpose of this study is what can be done to prevent the spread of such problems of the district. In this study, natural and cultural traits to be developped in the district of Eğirdir have been investigated and analized in order to detect the tourism and the recreational potentials in the region.